Effect of carbon supply mode on biomass and lipid in CSMCRI's Chlorella variabilis (ATCC 12198). (March 2016) - Patidar, Shailesh Kumar; Mitra, Madhusree; Goel, Sangita; Mishra, Sandhya
Abstract: CSIR-CSMCRI's Chlorella variabilis (ATCC 12198) was evaluated through autotrophic, mixotrophic and heterotrophic growth for lipid production. Autotrophic growth was assessed by providing sodium bicarbonate/sodium carbonate/CO2 (air in a medium). Higher lipid productivity (115.94 mg L −1  d −1 ) with higher biomass productivity (724.98 mg L −1  d −1 ) of this strain was attained through bicarbonate and CO2 sequestration in a photobioreactor. Ability to regulate the pH in favorable bicarbonate/carbonate ratio showed its potential in alkaline effluent based carbon sequestration system for biofuel generation. The simultaneous study was also conducted to understand the effect of elevated CO2 (0.4, 1 and 1.2 g L −1 ) in air on the culture to assess adaptation, growth and lipid in the closed chamber conditions. It was observed that CO2 sequestration by the microalgae from the CO2 enriched environment was optimum at 1 g L −1   C. variabilis adapted to comparatively higher CO2 (1 g L −1 ) but grew better in low CO2 (0.4 g L −1 ). It was also observed that the growth, lipid content and fatty acid composition was significantly affected by CO2 supply strategies. The effect of intermittently added sodium bicarbonate at different pH on microalgal lipid content and composition of fatty acids was observed which could affect the quality of biodiesel. The effect on fatty acid composition was observed in response to carbon supply mode during the microalgal growth at different pH dictating the properties of biodiesel. Graphical abstract: Highlights: Growth of C. Variabilis was checked by varying supply mode of inorganic carbon. Mixotrophic growth showed the highest lipid productivity using biodiesel glycerol. Fatty acid composition varied at different pH and varying carbon supply. High CO2 adapted cells showed higher biomass productivity under low CO2 condition.